A Technique for Estimating the Resilient Modulus (MR) of Unsaturated Soils from Modified California Bearing Ratio (CBR) Tests - Omenogor, Kenneth Onyekachi (Université d'Ottawa / University of Ottawa, 2022)
The Mechanistic-Empirical Pavement Design Guide (MEPDG) which is widely used for the rational design of pavements has three different design levels (i.e., Level 1, Level 2, and Level 3) that are typically based on the resources and the level of risk associated for a given project. Specifically, Level 2 design requires the estimation of the resilient modulus, MR (which is the key parameter in the mechanistic design procedures) from simple experiments such as the California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS) and R-value tests. In this study, a technique is proposed for estimation of MR from CBR that can be used in Level 2 designs of pavements. The California Bearing Ratio (CBR) is a relatively inexpensive laboratory test which provides a measure of the strength of a soil. The CBR test can easily be performed as the experimental procedure is relatively straightforward to execute. The CBR test procedure widely used and is simple, however the fundamental engineering principles governing CBR tests do not realistically describe the mechanical behavior of pavements. Due to this reason, there has been a significant interest to design pavements using a mechanistic approach such as the resilient modulus (MR). The MR test method provides an indication of the stiffness of pavement materials under cyclic loads, which closely represents the typical loading conditions that are experienced by pavements. MR is a reliable method as it considers the cyclic loading (i.e., resilient response) of pavements. However, it has one major drawback as the triaxial testing equipment used for measurement of the MR is relatively costly, testing is complex and requires trained professional to perform them. The CBR and MR are both used in present day practice to evaluate the strength of pavement materials. However, the CBR is widely used because of its relatively low cost and the vast experience with its use in the design of pavements. The common trend in today’s practice is to estimate the MR from CBR as evident in most pavement design procedures used around the world. For instance, the Mechanistic-Empirical Pavement Design Guide (AASHTO 2008) suggests that the MR may be estimated from standard tests like the CBR for design of Level 2 pavements. Numerous studies in the literature propose relationships between CBR and MR, but only a hand full of these studies takes account of the effect of matric suction, 𝜓 which is a key stress state variable that describes the rational behavior of unsaturated soils. This thesis document includes the explanation of a modified CBR test equipment capable of measuring unsaturated properties (𝜓 and water content) of specimens subjected to wetting and drying. In addition, some correlations were developed using the measured CBR data and the data of MR from other studies. The results provide useful information for Level 2 mechanistic-empirical design of pavement structures for various soils in the province of Ontario.
Keywords: California Bearing Ratio; Mechanistic Empirical Pavement Design; Resilient Modulus; Matric suction; Unsaturated soils; Subgrade soils; Pavement design